Framework to Approximate the Value of Information of Bridge Load Testing for Reserve Capacity Assessment - Bertola, Numa J.; Proverbio, Marco; Smith, Ian F. C. (Frontiers in Built Environment, 2020)
In developed countries, structural assessment of existing bridges should not be performed using the same conservative models that are used at the design stage. Field measurements of real behaviour provide additional information for the inference of previously unknown reserve capacity. Structural identification helps identify suitable models as well as values for parameters that influence behaviour. Since the information gained by the measurement system has a direct impact on structural identification, studies on optimal sensor placement have been extensively carried out. However, information collected during monitoring comes at a cost that may not be justified by its influence on asset-manager actions. A metric called value of information measures if the price of collecting information is justified when compared with the potential influence on asset-manager decision-making. This paper presents a framework to approximate the value of information of bridge load testing for reserve-capacity assessment. Additionally, an approach based on levels of approximation is used to provide a practical strategy for the assessment of the value of information. The framework provides guidance to asset managers to evaluate whether the information from controlled-condition monitoring, collected at a cost, may influence their assessment of reserve capacity. Several scenarios of monitoring systems are compared using their respective potential influence on asset-manager decisions and cost of monitoring, using a full-scale case study: the Exeter Bascule Bridge.